Evaluating People’s Character in the Jakarta Post News - Ayu Pusparini; Djatmika Djatmika; Riyadi Santosa (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2018)
This research belongs to descriptive qualitative research with the purposive sampling technique. The data for the research are collected from two news texts exposing Duo Bali Nine execution taken from the online version of The Jakarta Post. The purposes of the research are to identify the judgement used by the journalists and see the journalists’ attitude in presenting the character in their news report. The results show that the number of positive judgements in the text is more than the negative judgements. The subjectivity of the journalists used to support the Myu Sukumaran. Journalists also try to persuade the reader by up scaling the evaluations which support Sukumaran.